Decoding the Trends and Progress of Artificial Intelligence in E-commerce Over the Last Decade - As'ad, Ihwana (ZERO: Jurnal Sains, Matematika dan Terapan, 2025)
Through process improvement, growth acceleration, and business landscape transformation, artificial intelligence (AI) has transformed online businesses and accelerated digital transformation. The purpose of this study is to presents a conceptual overview of artificial intelligence (AI) in E-commerce. Potential research themes, explored through content analysis and visualization techniques, offer deeper understanding of the knowledge landscape in this field. This study utilized VOSviewer and R-bibliometrix to conduct data analysis and network visualization the scientific output of 811 research articles form Scopus, WoS and PubMed database from 2000 to 2024, including the number of publications, countries, journal, citations, authors, and keywords. The results of this research show that China and USA emerges as the country with the significant contributions to the development of research related to artificial intelligence in e-commerce, which is dominated by affiliations from Zhejiang University. In the analysis of the relationship between topics, two clusters were obtained, the most dominant topics with keyword “human” and “neural network”. Neural networks are included in AI algorithms that has characteristics similar to the human brain and have the ability to operate more efficiently and profitably in e-commerce. Researchers will gain important insights into the current landscape, as well as collaborative frameworks to suggest directions for future research.